Evaluation of the Effect of Decision Support Systems on the Quality of Managerial Decisions in MSME Companies in Indonesia - Kartini, Dewi; Hermawan, Rudi (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This study evaluates the impact of Decision Support Systems (DSS) on managerial decision quality in Indonesian Micro, Small, and Medium Enterprises (MSMEs), focusing on retail, food production, and textile sectors. Through a mixed-methods approach combining quantitative analysis of 150 MSMEs and qualitative interviews with 75 business owners, the research demonstrates significant improvements post-DSS implementation. Key findings include a 59.6% reduction in decision latency for micro-enterprises, 22.4% higher inventory turnover in retail businesses, and 18.3% improved margin stability in food production. The study identifies critical success factors such as Bahasa Indonesia interface localization (adoption rate 88%) and mobile-first design (SUS score 82.4/100), while highlighting infrastructure and digital literacy as persistent barriers. Comparative analysis reveals the solution outperforms previous implementations in developing markets, achieving break-even 40% faster. The research contributes both practical frameworks for DSS deployment in resource-constrained environments and theoretical extensions to technology acceptance models, emphasizing